2011
DOI: 10.1007/s11431-011-4300-9
|View full text |Cite
|
Sign up to set email alerts
|

The growth mechanism of the basic magnesium chloride whisker

Abstract: Based on the theoretical model of anion coordination polyhedron growth units, the growth mechanism of the basic magnesium chloride whisker was discussed in this paper. It was found that the basic magnesium chloride whisker habits were related to the different environments in which anion coordination polyhedra grew. The growth units of basic magnesium chloride whiskers are 2 4 [Mg (OH) ]   and 2 4 [Mg Cl ] .  The growth process is the incorporation process of growth units. Growth units will have different i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…6 shows the SEM images of the samples, the results show that the whisker shape maintained still very well in the Mg(OH)2. The fact of the basic magnesium chloride wkiskers can be transformed into Mg(OH)2 whiskers by base NaOH treatment provided an evidence of that the Cl anions were rather than the structure of the free in the basic magnesium chloride wkiskers 2,5,8 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 shows the SEM images of the samples, the results show that the whisker shape maintained still very well in the Mg(OH)2. The fact of the basic magnesium chloride wkiskers can be transformed into Mg(OH)2 whiskers by base NaOH treatment provided an evidence of that the Cl anions were rather than the structure of the free in the basic magnesium chloride wkiskers 2,5,8 .…”
Section: Resultsmentioning
confidence: 99%
“…They have similar molecular structure and same function characteristics of the enhancement, flame retardant and filler application in engineering plastic 1 . The basic magnesium chloride whiskers with a general formula of xMg(OH) 2 •yMgCl 2 •zH 2 O (x = 2,3,5,9; y = 1; z = 1,2,3…..) 2,3 were discovered and applied in cement 4 . The basic magnesium chloride whiskers could generally be synthesized in a typical method by using magnesium oxide powder and magnesium chloride solution as raw materials [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the fact that the improved hydrothermal method has great advantages [7][8][9] , the synthesis and characterization of basic oxysulfate magnesium whiskers were done according to a previous paper [10] . Using the hydrothermal method, a solution with 25% volume fractions of butanol was prepared, and then solutions of 0.1 mol·L −1 MgSO 4 ·7H 2 O and 0.1 mol·L −1 of NaOH were prepared by using the butanol solution as diluent.…”
Section: Methodsmentioning
confidence: 99%
“…Magnesium hydroxide has potential applications in various fields, due to the fact that it is capable of greatly increasing the strength, rigidity, dimensional stability, and deformation temperature of plastic. 1,2 Previous studies have reported on the development and application of magnesium hydroxide whiskers. However, recent research concerning magnesium hydroxide whiskers has not provided reasonable explanations for the following problems: first, what is the unit cell structure of magnesium hydroxide whiskers?…”
Section: Introductionmentioning
confidence: 99%